2021
DOI: 10.1111/are.15101
|View full text |Cite
|
Sign up to set email alerts
|

The use of dietary oak acorn extract to improve haematological parameters, mucosal and serum immunity, skin mucus bactericidal activity, and disease resistance in rainbow trout (Oncorhynchusmykiss)

Abstract: Medicinal plants have been successfully used to enhance the growth and immunity of fish during recent decade. The experiments herein were designed to assess the dietary effects of oak acorn (Quercus brantii) extract (OAE) on blood parameters, serum and skin mucus immune responses and resistance antibacterial activities of rainbow trout (Oncorhynchus mykiss) skin mucus against Yersinia ruckeri and Streptococcus iniae. Four hundred and fifty fingerlings (10.45 ± 0.24 g) were randomly stocked in fifteen tanks and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 88 publications
(115 reference statements)
0
11
0
Order By: Relevance
“…Dietary supplements, including plant‐based supplements, are currently used to keep health and to treat many diseases in humans and animals (Fattepur et al, 2018; Gondo, 2021; Othman et al, 2019; Roslan & Shariff, 2021; Shalaby, 2015, 2018; Shalaby, Sakoury, Harthi, et al, 2020; Shalaby, Sakoury, Kholif, et al, 2020; You et al, 2021; Zharif et al, 2018). During the last decade, many studies have reported the medicinal, antioxidant, immunogenic and antibacterial properties of medicinal plants and their derivatives in fish (Ahmadifar et al, 2019; Farsani et al, 2019; Rashidian, Bahrami Gorji, et al, 2020; Van Doan et al, 2020; Bibi et al, 2021; DeiviArunachalam et al, 2021; Ghafarifarsani Kachuei et al, 2021; Ghafarifarsani, Hoseinifar, Adorian, et al, 2021; Ghafarifarsani, Hoseinifar, Talebi, et al, 2021; Ghafarifarsani, Rashidian, et al, 2021; Qahir et al, 2021; Rashidian et al, 2021; Yousefi, Farsani, et al, 2021; Yousefi, Ghafarifarsani et al, 2021; Raissy et al, 2022; Yousefi et al, 2022). However, the identification and introduction of the new species with immunogenic and antibacterial properties can be useful for aquaculture enhancement.…”
Section: Introductionmentioning
confidence: 99%
“…Dietary supplements, including plant‐based supplements, are currently used to keep health and to treat many diseases in humans and animals (Fattepur et al, 2018; Gondo, 2021; Othman et al, 2019; Roslan & Shariff, 2021; Shalaby, 2015, 2018; Shalaby, Sakoury, Harthi, et al, 2020; Shalaby, Sakoury, Kholif, et al, 2020; You et al, 2021; Zharif et al, 2018). During the last decade, many studies have reported the medicinal, antioxidant, immunogenic and antibacterial properties of medicinal plants and their derivatives in fish (Ahmadifar et al, 2019; Farsani et al, 2019; Rashidian, Bahrami Gorji, et al, 2020; Van Doan et al, 2020; Bibi et al, 2021; DeiviArunachalam et al, 2021; Ghafarifarsani Kachuei et al, 2021; Ghafarifarsani, Hoseinifar, Adorian, et al, 2021; Ghafarifarsani, Hoseinifar, Talebi, et al, 2021; Ghafarifarsani, Rashidian, et al, 2021; Qahir et al, 2021; Rashidian et al, 2021; Yousefi, Farsani, et al, 2021; Yousefi, Ghafarifarsani et al, 2021; Raissy et al, 2022; Yousefi et al, 2022). However, the identification and introduction of the new species with immunogenic and antibacterial properties can be useful for aquaculture enhancement.…”
Section: Introductionmentioning
confidence: 99%
“…In the present study, the infected rainbow trout with Y. ruckeri indicated a significantly lower mortality rate in the LE-added groups, especially in LE2 treatment, compared with the control group. The positive effect of various medicinal plants in increasing the survival rate of rainbow trout against yersiniosis has been previously reported (23,57,66,70,71). The increase in the survival and resistance of rainbow trout against Y. ruckeri infection in LE 2 and LE3 treatments can confirm the enhancement of the fish innate immunity and health, which are in line with the improvements in the measured immune parameters of serum and skin mucus.…”
Section: Discussionmentioning
confidence: 80%
“…For instance, Gholamhosseini et al ( 56 ) showed that dietary Tarragon ( Artemisia dracunculus ) improved LYZ and ALP activity and TP value in rainbow trout. In another study, Ghafarifarsani et al ( 57 ) indicated that rainbow trout fed diet enriched with oak acorn ( Quercus liaotungensis ) extract had remarkably higher skin mucus LYZ and ALP activities compared with the control group. The beneficial effects of licorice on the immune responses may be due to immunomodulatory compounds such as glycyrrhizin, which was previously reported ( 18 20 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…are a diverse group of plants with ecologically, economically, and medicinal importance that are widely distributed in the forests of temperate‐cold climate. Several studies have reported the antimicrobial and antioxidant effects of the acorn extract in some fishes, such as rainbow trout (Bohlouli et al, 2016; Ghafarifarsani et al, 2021; Rashidian et al, 2020) and common carp (Paray et al, 2020; Raissy et al, 2022). Oak leaf extract stimulates the antioxidant and immune system of common carp, without affecting the fish growth performance (Paray et al, 2020).…”
Section: Introductionmentioning
confidence: 99%